Análisis y reestructuración de los procesos comerciales en la Corporación Nacional de Electricidad de la Regional Santo Domingo - Asanza Asanza, Martha Judith (2012)
Existing business processes in the National Electricity Corporation Santo Domingo for the most part are partially automated, resulting in a lack of understanding in them since the processes are not fully defined, resulting in delay in implementation of activities by lack of implementation of new technology, making teamwork and meeting corporate objectives. In forming a corporation where they are integrated 10 Utilities, lifting necessary processes to have the information needed and perform an evaluation to establish a model that will serve as an example for other regional make up the National Electricity Corporation.